Plasmodium Falciparum and mosquito vector IgG patterns across suspected malaria cases in Ghana - Kwame Kumi Asare; Sebastian Shine Kwapong; Prosper Tey; Vincent Sackey; Samuel Victor Nuvor; Linda Eva Amoah (BMC Infectious Diseases)
Abstract Introduction Malaria, a widespread tropical disease, remains a significant global health issue, resulting in numerous deaths each year. In Ghana, malaria is a leading cause of illness, contributing to a large proportion of hospital outpatient visits. The study assessed the pattern of malaria and vector IgG antibody levels among suspected malaria patients seeking healthcare at selected health facilities across Ghana. Methods Samples from a total of 823 participants aged 1 to 85 years with clinical malaria from the ten regions of Ghana were recruited into the study. Archived plasma obtained from each participant was used to assess antibody responses against MSP1 (19 k), MSP2 (FC27 & 3D7), MSP3, gSG6-P1, and GLURP-RO using ELISA. The data were categorized according to study site, age group, gender, and diagnostic tests. Data were analyzed using Kruskal–Wallis’s statistics. The statistical significance was assessed at 0.05. Results The mean ± standard error of the mean (S.E) of MSP3 IgG concentration for the different age groups were 16, 847 ± 3, 031 ng/mL for 0–4 years, 18, 973 ± 4,357 ng/mL for 5–10 years, 25,961 ± 5,436 ng/mL for 11–15 years and 76, 244 ± 8, 209 ng/mL for ≥ 16 years. A significant (Kruskal–Wallis statistic = 122.6, p < 0.0001) increase in P. falciparum MSP 3 (p < 0.0001) and gSG6-P1(p < 0.0001) IgG concentration was observed with increasing age categories. There were significant differences in antibody responses against MSP2 (FC27) IgG (Kruskal–Wallis statistic = 29.63, p = 0.0005), MSP3 IgG (Kruskal–Wallis statistic = 32.53, p = 0.0002), GLURP-RO IgG (Kruskal–Wallis statistic = 52.8, p < 0.0001) and gSG6-P1 IgG (Kruskal–Wallis statistic = 152.8, p < 0.0001) across the study regions. Conclusion The study reveals that IgG against merozoite surface proteins MSP3, GLURP-RO, and gSG6-P1 but not MSP1 and MSP2 antibodies increase with age. The mean IgG antibody concentrations varied in the selected regions of Ghana. A longitudinal study where confounding factors are controlled for is recommended to provide insights into the development of immunity and antibody efficacy, and to enhance the effectiveness of malaria prevention efforts in Ghana. This will help improve the overall understanding of malaria transmission.